Metabolic Mechanisms of Exercise-Induced Cardiac Remodeling - Fulghum, Kyle; Hill, Bradford G. (Frontiers in Cardiovascular Medicine, 2018)
Exercise has a myriad of physiological benefits that derive in part from its ability to improve cardiometabolic health. The periodic metabolic stress imposed by regular exercise appears fundamental in driving cardiovascular tissue adaptation. However, different types, intensities, or durations of exercise elicit different levels of metabolic stress and may promote distinct types of tissue remodeling. In this review, we discuss how exercise affects cardiac structure and function and how exercise-induced changes in metabolism regulate cardiac adaptation. Current evidence suggests that exercise typically elicits an adaptive, beneficial form of cardiac remodeling that involves cardiomyocyte growth and proliferation; however, chronic levels of extreme exercise may increase the risk for pathological cardiac remodeling or sudden cardiac death. An emerging theme underpinning acute as well as chronic cardiac adaptations to exercise is metabolic periodicity, which appears important for regulating mitochondrial quality and function, stimulating metabolism-mediated exercise gene programs and hypertrophic kinase activity, and coordinating biosynthetic pathway activity. In addition, circulating metabolites liberated during exercise trigger physiological cardiac growth. Further understanding of how exercise-mediated changes in metabolism orchestrate cell signaling and gene expression could facilitate therapeutic strategies to maximize the benefits of exercise and improve cardiac health.